Measurement of Student Cognitive Loads on Course Kapitaselekta Mathematics - Asmara, A.S; Fitri, Ayu; Gunanta, Remon (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to measure intrinsic cognitive load, extraneous cognitive load, and germane cognitive load students in the elementary school teacher education program (PGSD) at the Kapitaselekta lecture and how is the relationship between the three cognitive load components of PGSD students in the Kapitaselekta Mathematics lecture. This study uses a qualitative approach with descriptive research methods that aim to get a picture of the cognitive burden of PGSD students in the Kapitaselekta Mathematics lecture. The research subjects were PGSD students who contracted the Kapitaselekta Mathematics course in the 2018/2019 Academic Year as many as 50 students. Data analysis showed that the three components of the cognitive load filter correlated significantly even though the correlation was weak for several sub-concepts at the Kapitaselekta Mathematics.